Optimizing active recovery strategies for finger flexor fatigue - Krupková, Dominika; Tufano, James J.; Baláš, Jiří (Frontiers in Sports and Active Living, 2024)
Introduction Active recovery (AR) is used during exercise training; however, it is unclear whether the AR should involve the whole body, only the upper extremities, or only the lower extremities when aiming to maintain localized upper body performance. Therefore, this study aimed to evaluate the impact of different AR strategies on repeated intermittent finger flexor performance leading to exhaustion. Methods A crossover trial involving a familiarization session and three laboratory visits, each including three exhaustive intermittent isometric tests at 60% of finger flexor maximal voluntary contraction separated by 22 min of randomly assigned AR: walking, intermittent hanging, and climbing. Results The impulse (Nꞏs) significantly decreased from the first to third trials after walking (−18.4%, P = 0.002, d = 0.78), climbing (−29.5%, P < 0.001, d = 1.48), and hanging (−27.2%, P < 0.001, d = 1.22). In the third trial, the impulse from the intermittent test was significantly higher after walking (21,253 ± 5,650 Nꞏs) than after hanging (18,618 ± 5,174 Nꞏs, P = 0.013, d = 0.49) and after climbing (18,508 ± 4,435 Nꞏs, P = 0.009, d = 0.54). Conclusions The results show that easy climbing or intermittent isolated forearm contractions should not be used as AR strategies to maintain subsequent performance in comparison to walking, indicating that using the same muscle group for AR should be avoided between exhaustive isometric contractions.